All-optical microwave oscillator based on a mutual-injection coupling between DFB-LDs - Tang, Jian; Bai, Guangfu; Tang, Yanling; Xu, Liang; Wang, Guangxin; Shang, Dunsheng; Jiang, Yang (Optics express, 2022)
An all-optical microwave oscillator (AOMO) is proposed and experimentally demonstrated. It contains only a mutual injection loop consisting of two distributed feedback laser diodes (DFB-LDs) and a few passive components. In this AOMO, the microwave seed signal originates from the period-one (P1) oscillation in one of the DFB-LDs. The functions of microwave envelope detection and feedback modulation are implemented by the other DFB-LD. Due to the optical injection locking and the optical-optical modulated effect in DFB-LD, the P1 signal is enhanced, and the stability of the P1 signal can be improved by coupling the P1 signal with a resonant mode of the mutual injection loop. Meanwhile, since the P1 oscillation is sensitive to injected light, the frequency of the P1 signal can be easily adjusted, which makes the AOMO easy to be tuned. In the experiment, a highly stable single-mode microwave signal with a frequency of 16.69 GHz and a single-sideband (SSB) phase noise of −90.7 dBc/Hz@10 kHz is generated. The frequency can be tuned from 14.48 to 21.45 GHz by adjusting the parameters of DFB-LDs and the injection light.